The Influence of Financial Risk Disclosure on Earning Qualities among Cross-Listed Companies in the UK - Bi, Zheng (2017)
This dissertation investigates the impact of financial risk disclosure for 25 cross-listed companies in the UK from 2007 to 2016 on earning qualities. Unlike the previous studies which consider the whole risk disclosure, the current study focuses only on financial risk disclosure and finds that there is a negative effect of financial risk disclosure on earning qualities. Further, foreign exchange rate risk of the main five types of financial risks (credit risk, liquidity risk, interest rate risk, foreign exchange rate risk and commodity price risk) is confirmed as the part which leads to the significant influence on earning qualities and thus to which financial managers need pay more attention.